Re-absorption of former civil servants and the appiontment of Central Eastern States indigenes in the Federal public services and other public services of the Federarion (Lagos, Nigeria Federal Ministry of Information, 1970)
This publication goes a long way to demonstrate that adequate steps have been taken to protect the interest of the people of the Central Eastern State.
Statement by the public Federal Public Service commission, Lagos.
nmn, 21/03/19
Arch
Keywords: Federal civil service; Reabsorbtion, appointment; Federal public service; Central Eastern State, Nigeria